Experimental and numerical study of solidifying phase-change material in a triplex-tube heat exchanger with longitudinal/triangular fins. (January 2018) - Abdulateef, Ammar M.; Abdulateef, Jasim; Mat, Sohif; Sopian, Kamaruzzaman; Elhub, Bashir; Mussa, Munther Abdullah
Abstract: Latent heat thermal energy storage (LHTES) system uses a large triplex-tube heat exchanger (TTHX) with internal longitudinal fins incorporating phase-change material (PCM) was experimentally designed, tested, and evaluated. The PCM was entirely solidified using the both-sides freezing, as a main method under the influence of average discharging temperature was at 65 °C. The changes in the mass flow rates of 16.2, 29.4, and 37.5 min/kg were investigated. The solidification rate increased, as the mass flow rate increased, therefore the mass flow rate at 37.4 kg/min consumed a short time, compared with the 16.2 and 29.4 kg/min. Furthermore, the PCM completely solidified, as fast as at position B than position A from the entrance of the HTF-tube because of temperature variations in axial and angular direction during discharging process. Two types of extended surfaces, namely the longitudinal and triangular fins in various configuration were numerically studied. A significant enhancement was observed using internal, internal-external, and external triangular fins at 14%, 16%, and 18% respectively, compared to longitudinal fins configuration. Consequently, the external triangular finned tube has been considered the most efficient for the brief solidification PCM (630 min). The total energy released for the both types of fins were compared. The simulation results were agreed well with the experimental results. Highlights: The PCM solidification for both-sides freezing was experimentally accomplished at 65 °C. Longitudinal and triangular fins model of the TTHX were numerically studied. The influence of change in the mass flow rates during discharging process was investigated. External triangular fins model was the most efficient for shorter solidification time (630 min).